2020
DOI: 10.1038/s42003-020-01461-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic ancestry, skin pigmentation, and the risk of cutaneous squamous cell carcinoma in Hispanic/Latino and non-Hispanic white populations

Abstract: Although cutaneous squamous cell carcinoma (cSCC) is one of the most common malignancies in individuals of European ancestry, the incidence of cSCC in Hispanic/Latinos is also increasing. cSCC has both a genetic and environmental etiology. Here, we examine the role of genetic ancestry, skin pigmentation, and sun exposure in Hispanic/Latinos and non-Hispanic whites on cSCC risk. We observe an increased cSCC risk with greater European ancestry (P = 1.27 × 10−42) within Hispanic/Latinos and with greater northern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…Genetic studies to date have identified few syndromes associated with increased risk of SCC (including xeroderma pigmentosa, epidermolysis bullosa, Fanconi anaemia, oculocutaneous albinism and aging syndromes such as Werner syndrome), and BCC (Basal cell nevus syndrome), some higher risk genes which are primarily pigment related (MC1R, OCA2, HER2, TYR, ASIP, SCL45A2, IRF4) and HLA ( HLADQA1 ) 21,22 . More recently an ancestry gene effect in Hispanic and non‐Hispanic whites 23 was demonstrated. Like CLCN6, most of these variants show small effect sizes with typical odds ratios ranging from 1.15 to 1.5.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies to date have identified few syndromes associated with increased risk of SCC (including xeroderma pigmentosa, epidermolysis bullosa, Fanconi anaemia, oculocutaneous albinism and aging syndromes such as Werner syndrome), and BCC (Basal cell nevus syndrome), some higher risk genes which are primarily pigment related (MC1R, OCA2, HER2, TYR, ASIP, SCL45A2, IRF4) and HLA ( HLADQA1 ) 21,22 . More recently an ancestry gene effect in Hispanic and non‐Hispanic whites 23 was demonstrated. Like CLCN6, most of these variants show small effect sizes with typical odds ratios ranging from 1.15 to 1.5.…”
Section: Discussionmentioning
confidence: 99%
“…Even though phenotypic characteristics have been broadly described, the genetic structure of the population has rarely been highlighted, particularly in the quest to establish correlations between prevalence and geographic distribution [ 53 ]. Analyses of the rs357564 variant have been performed in several types of cancer and clinical conditions [ 54 , 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…European alleles were selected as the prevalence of cSCC is highest in individuals of European descent. 23 Overall, 24/149 patients (16.1%) contain a shared mutation that is predicted to bind well to MHC class I (Fig. 1d).…”
Section: Majority Of Mutations In Human Cscc Are Unique To Individual...mentioning
confidence: 99%